Analysis of the main factors affecting the lives of workers and accidents at industrial enterprises of the Republic - Ruziyev S.T; Sobirov Sh.N. (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the importance of the organization of labor protection at the enterprise, their impact on the end result of production activities, a brief comparative analysis with foreign experience. Also, the main factors affecting the state of safety of workers in production are considered, and ways of solving emerging problems in the field of labor protection are proposed.